APPLYING RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING AND CAPITAL (RGEC) METHOD TO PREDICT THE BANK HEALTH (CASE STUDY ON PT. BANK TABUNGAN NEGARA) - Zainuddin, Zainuddin; Djaelani, Yustiana (Universitas Sam Ratulangi, 2018)
This study aimed to analyze the health of PT. Bank Tabungan Negara (Persero) Tbk over period of 2013 to 2017 RGEC method approach (Risk Profile, Good Corporate Governance, Earnings, Capital). This research is quantitative descriptive method. The variables in this study include Risk Profile using the ratio of Non Performing Loans (NPLs) and loan to Deposits Ratio (LDR), GCG using Composite Rating GCG, Earnings use ratios Return on Assets (ROA) and Net Interest Margin (NIM) and Last Capital uses Adequacy Capital ratio (CAR). The results showed Bank BTN predicate healthy enough where banks are still quite capable of carrying out risk-based banking management well, so they deserve to be trusted community. However, the calculation of the proportion of Loan to Deposits Ratio (LDR) is below standard bank of Indonesia with the predicate less healthy.